PRACTICE OF FORMING CULTURE OF DIALOGIC SPEECH OF NONPHILOLOGICAL STUDENTS - Оксана Орлова (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article deals with determination of the state of forming culture of dialogic speech (CDS) of nonphilological students. The educational curriculums and textbooks on professional Ukrainian have been analysed the correspondence of one textbook to the curriculum has been distinguished. With the help of the developed exercises the pre-experimental test has been conducted and its quantative and qualitative results have been estimated on the basis of the criteria. These results lead to creating experimental curriculum of CDS formation and devising its methodology.